Malnutrition in Non-Hodgkin Lymphoma Patients at Dr. Hasan Sadikin General Hospital Bandung - Azizah Puspitasari Ardinal; Siska Wiramihardja; Indra Wijaya (Althea Medical Journal, 2019)
Background: Non-hodgkin lymphoma (NHL) has the highest prevalence among hematologic malignancies. The prognosis and response to therapy in NHL patients may worsen in the presence of malnutrition. The aim of the study was to describe the malnutrition status in NHL patients. Methods: This was a cross-sectional descriptive study. Nutritional status was assessed using Subjective Global Assessment (SGA) obtained from the medical records of all NHL patients at Dr. Hasan Sadikin General Hospital registered in 2017.Results: In total, there were 78 medical records of NHL patients that fulfilled the inclusion criteria. All NHL patients had experienced malnutrition, categorized as mild-moderate malnutrition (70.5%) and severe malnutrition (29.5%). In NHL patients with mild-moderate malnutrition, 29% had 5–10% weight loss; 60% had suboptimal solid diet; 56.4% experienced anorexia; and 50.9% had subcutaneous fat loss. In NHL patients with severe malnutrition, 78.3% had more than 10% weight loss; 73.9% had suboptimal solid diet; 78.3% experienced anorexia; and 100% had subcutaneous fat loss.Conclusions: Based on subjective assessment, all NHL patients were malnourished and experienced change of food intake and loss of subcutaneous fat, therefore, a better nutritional support scheme are crucial for NHL patients.